AB0241 Rheumatoid Arthritis Patients in Australian Database Show Significant Improvement in Disease Activity over 5 Years. (10th June 2014) - Littlejohn, G.; Roberts, L.; Bird, P.; de Jager, J.; Griffiths, H.; Nicholls, D.; Young, J.; Zochling, J.; Tymms, K.E.
Abstract : Background: Rheumatoid arthritis (RA) treatment in Australia has undergone significant change in the last decade. New treatment paradigms of treat to target, with remission being the goal, supplemented by maintenance of tight control have become standard of care. We have established a network database, named OPAL-QUMI (O ptimising P atient outcome in A ustralian RheumatoL ogy – Quality Use of Medicines) whereby patient-specific details are captured on purpose-written software at the time of consultation. This information represents real-life data reflecting everyday care of the patient. We used this database to assess surrogates of disease activity over the 5-year period that our consortium has been in place (2009-2013). Objectives: To evaluate the disease activity trends in rheumatoid arthritis (RA) patients in Australia over 5 years. Methods: RA patients treated in participating Australian clinics were included in the study. Patient demographics, disease onset, medications and disease measures were analysed. Data, de-identified to the patient, clinic and clinician was captured using an electronic clinical management programme. The disease activity score (DAS28) was used to classify patients into the disease activity states of remission, low disease activity (LDA), moderate disease activity (MDA) and high disease activity (HDA). Choice of therapy was at the discretion of the treating clinician. Results: A total of 8, 458 patients, 72.3% female, 27.3% male with mean age 62.1 (SD 13.9) years and mean disease duration of 13.0 (SD 10.9) years were analysed. There were 31, 023 individual DAS28 ESR values recorded in the patient group. Of these patients 45.6% were in remission, 17.1% in LDA, 28.1% in MDA and 9.2% in HDA. The percentage of patients in remission increased from 37.4% (2009) to 52.5% (2013) over the 5-year analysis period, with those in MDA falling from 32.7% to 23.5%, with reduction also in LDA from 19.1% to 16.15% and HDA from 10.8% to 7.9%. The use of biologic disease modifying antirheumatic drugs increased from 22.8% to 37.9% over the same time period. Conclusions: Serial cross-sectional assessment of this large cohort of Australian RA patients showed significant increases in lower disease activity scores, with more patients in the remission and less in moderate disease activity groups over 5 years. Contemporary management of RA in Australia shows improvement in disease activity targets. Disclosure of Interest: G. Littlejohn: None declared, L. Roberts: None declared, P. Bird: None declared, J. de Jager: None declared, H. Griffiths: None declared, D. Nicholls: None declared, J. Young Employee of: Roche Products, Pty. Limited, J. Zochling: None declared, K. Tymms: None declared DOI: 10.1136/annrheumdis-2014-eular.4834